Real or fake?. 3 : even more far-out fibs, fishy facts, and phony photos to test for the truth - Krieger, Emily (National Geographic kids., 2018)
Presents a collection of odd facts, findings, and photographs and asks readers to determine whether they are true or fake. Features quizzes, color photographs, and fact boxes.